Struktur Sistem Operasi Windows dalam Mendukung Kinerja Operasional - Ramadhan Ardi Iman Prakoso; Anindha Latiefa Zahra; Elkin Rilvani (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
The structure of the Windows operating system plays an important role in supporting the operational performance of computers, especially in business environments and professional users. This system is designed with a modular and layered architecture, which includes various components such as Hardware Abstraction Layer (HAL), I/O device manager, virtual memory management, and an integrated security system. Windows also supports energy management and plug-and-play mechanisms, which improve power efficiency and hardware compatibility. This architectural approach allows Windows to optimize interactions between hardware and applications, supports multitasking, and provides an efficient user interface. Thus, the structure of the Windows operating system is able to significantly improve device performance, which leads to optimization of operational performance.